1996
DOI: 10.1103/physrevd.54.3526
|View full text |Cite
|
Sign up to set email alerts
|

Heavy quark spectroscopy and matrix elements: A lattice study using the static approximation

Abstract: We present results of a lattice analysis of the B parameter B B , the decay constant f B , and several mass splittings using the static approximation. Results were obtained for 60 quenched gauge configurations computed at ␤ϭ6.2 on a lattice size of 24 3 ϫ48. Light quark propagators were calculated using the O(a)-improved Sheikholeslami-Wohlert action. We findcorresponding to B B static ϭ1.02 Ϫ6 Ϫ2 ϩ5 ϩ3 , f B static ϭ266 Ϫ20 Ϫ27 ϩ18 ϩ28 MeV, and f B s 2 B B s / f B 2 B B ϭ1.34 Ϫ8 Ϫ3 ϩ9 ϩ5 , where a variational… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 65 publications
(129 reference statements)
6
70
0
Order By: Relevance
“…After we finished the first analysis of our data [13], we found that our value for B B was approximately 30% higher than the result of a similar simulation by the UKQCD collaboration [21]. We suspected that this difference was due to more than just the difference in the actions.…”
Section: Perturbative Matchingmentioning
confidence: 81%
“…After we finished the first analysis of our data [13], we found that our value for B B was approximately 30% higher than the result of a similar simulation by the UKQCD collaboration [21]. We suspected that this difference was due to more than just the difference in the actions.…”
Section: Perturbative Matchingmentioning
confidence: 81%
“…MC data for the ground state energy E MC of a static-light meson with the Wilson gauge action can be found in Refs. [42][43][44]. While for the gluon condensate we expected an a 4 -scaling (see Fig.…”
mentioning
confidence: 94%
“…[4], UKQCD coll. [12], Christensen et al [13] and also by JLQCD coll. in NRQCD when their results are extrapolated to the infinite mass limit [14].…”
Section: B-parameters From Numerical Simulations On the Latticementioning
confidence: 99%